Linkage to Primary Care and Survival After Hospital Discharge for HIV-Infected Adults in Tanzania: A Prospective Cohort Study. (15th December 2016) - Peck, Robert N.; Wang, Richard J.; Mtui, Graham; Smart, Luke; Yango, Missana; Elchaki, Rim; Wajanga, Bahati; Downs, Jennifer A.; Mteta, Kien; Fitzgerald, Daniel W.
Abstract : Introduction: Little is known about outcomes after hospitalization for HIV-infected adults in sub-Saharan Africa. We determined 12-month, posthospital mortality rates in HIV-infected vs. uninfected adults and predictors of mortality. Methods: In this prospective cohort study, we enrolled adults admitted to the medical wards of a public hospital in northwestern Tanzania. We conducted standardized questionnaires, physical examinations, and basic laboratory analyses including HIV testing. Participants or proxies were called at 1, 3, 6, and 12 months to determine outcomes. Predictors of in-hospital and posthospital mortality were determined using logistic regression. Cox regression models were used to analyze mortality incidence and associated factors. To confirm our findings, we studied adults admitted to another government hospital. Results: We enrolled 637 consecutive adult medical inpatients: 38/143 (26.6%) of the HIV-infected adults died in hospital vs. 104/494 (21.1%) of the HIV-uninfected adults. Twelve-month outcomes were determined for 98/105 (93.3%) vs. 352/390 (90.3%) discharged adults, respectively. Posthospital mortality was 53/105 (50.5%) for HIV-infected adults vs. 126/390 (32.3%) for HIV-uninfected adults (adjusted P = 0.006). The 66/105 (62.9%) HIV-infected adults who attended clinic within 1 month after discharge had significantly lower mortality than the other HIV-infected adults [adjusted hazards ratio = 0.17 (0.07–0.39), P < 0.001]. Adults admitted to a nearby government hospital had similar high rates of posthospital mortality. Conclusions: Posthospital mortality is disturbingly high among HIV-infected adult inpatients in Tanzania. The posthospital period may offer a window of opportunity to improve survival in this population. Interventions are urgently needed and should focus on increasing posthospital linkage to primary HIV care. Abstract : Supplemental Digital Content is Available in the Text.